Stable Intronic Sequences and Exon Skipping Events in the Human RPE65 Gene: Analysis of Expression in Retinal Pigment Epithelium Cells and Cell Culture Models - Postnikova, Olga; Poliakov, Eugenia; Golestaneh, Nady; Rogozin, Igor B.; Redmond, T. Michael (Frontiers in Genetics, 2019)
Currently there is much interest in intronic sequence-containing lncRNAs and the role of intronic transcription in regulation of cellular metabolism and fate. Several stable intronic sequences RNAs (sisRNAs) were recently implicated in regulation of parental genes. To investigate transcription from introns of the RPE65 gene we analyzed RNA-seq data from different cell models of human retinal pigment epithelium (RPE) and native bovine RPE. We discovered stable poly-adenylated transcripts with sequences corresponding to intronic regions of RPE65 gene in cytoplasm of RPE cells. These stable intronic lncRNAs could be important for RPE65 splicing or translation. Also, they might have positive or negative feedback loop on transcription of RPE65 mRNA.